(untitled) (Universal International Scientific Journal, 2026)
A country that does not take care of children and youth has no future, and unless there are significant changes in the near future, we are doomed to extinction. Youth is a socio-demographic group experiencing social maturity, adaptation to the adult world, and future changes. Young people have fluid boundaries of their age, they depend on socio-economic development of society, the level of culture, living conditions. To consider the problems of youth, it is necessary to imagine what youth is, how it differs from other social groups.